2020
DOI: 10.1111/cmi.13282
|View full text |Cite
|
Sign up to set email alerts
|

Using genetically encoded heme sensors to probe the mechanisms of heme uptake and homeostasis in Candida albicans

Abstract: Candida albicans is a major fungal pathogen that can utilise hemin and haemoglobin as iron sources in the iron‐scarce host environment. While C. albicans is a heme prototroph, we show here that it can also efficiently utilise external heme as a cellular heme source. Using genetically encoded ratiometric fluorescent heme sensors, we show that heme extracted from haemoglobin and free hemin enter the cells with different kinetics. Heme supplied as haemoglobin is taken up via the Common in Fungal Extracellular Mem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…Hemolytic activity is another virulence factor exhibited by pathogenic microorganisms, which enables fungal pathogens to utilize hemoglobin as an iron source for growth in the iron-scarce host environment ( Weissman et al., 2021 ). Previous studies have shown a close relationship between cellular iron and drug susceptibility in C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemolytic activity is another virulence factor exhibited by pathogenic microorganisms, which enables fungal pathogens to utilize hemoglobin as an iron source for growth in the iron-scarce host environment ( Weissman et al., 2021 ). Previous studies have shown a close relationship between cellular iron and drug susceptibility in C .…”
Section: Discussionmentioning
confidence: 99%
“…Hemolytic activity is another virulence factor exhibited by pathogenic microorganisms, which enables fungal pathogens to utilize hemoglobin as an iron source for growth in the ironscarce host environment (Weissman et al, 2021). Previous studies have shown a close relationship between cellular iron and drug susceptibility in C. albicans (Prasad et al, 2006), and iron uptake mechanisms have also been reported to be necessary for the virulence of C. glabrata (Figueiredo-Carvalho et al, 2017).…”
Section: Species Strains Numbermentioning
confidence: 99%
“…higher cytoplasmic heme concentrations. To expand the range of testable concentrations, a lower-affinity cytochrome domain mutant (M7A) can be used alongside the high-affinity original sensor (HS1) (Hanna et al, 2016; Weissman et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In C. albicans , it has been reported that the activity of HMX1 has a major contribution to its pathogenicity. This may be in relation to the utilization of iron directly, from host heme and heme proteins such as hemoglobin [ 28 ], but recently, CaHmx1’s role was found to be more centered around heme detoxification in C. albicans [ 29 ]. The localization of CaHmx1 in the cell is still unclear, and other enzymes involved in free heme and hemoglobin heme utilization have not yet been determined either ( Figure 1 a) [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be in relation to the utilization of iron directly, from host heme and heme proteins such as hemoglobin [ 28 ], but recently, CaHmx1’s role was found to be more centered around heme detoxification in C. albicans [ 29 ]. The localization of CaHmx1 in the cell is still unclear, and other enzymes involved in free heme and hemoglobin heme utilization have not yet been determined either ( Figure 1 a) [ 29 , 30 , 31 ]. The binding and uptake of free heme and hemoglobin-heme is possible through CFEM (common in several fungal extracellular membrane proteins) domain-containing proteins, namely Rbt5, Rbt51/Pga10, Pga7, and Csa2 [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%